Energy economic expansion with production and consumption in BRICS countries - Hasan M (Elsevier Ltd, 2022)
Global energy demand for energy consumption is increasing day by day, and it seems complicated for most countries to meet energy demand with total energy production. In this regard, this study investigates the comparative impact of energy production and consumption on economic growth in the BRICS countries. This study conducts panel data modelling, more specifically, the fixed-effects model, random-effects, and panel FMOLS model, to find the impact of energy production and consumption on economic growth in the BRICS countries. This study finds that energy production and consumption significantly impact the economic development of the BRICS countries. More specifically, dry natural gas production and consumption, electricity generation and consumption, biofuel production, petroleum production, capital formation, and trade openness positively impact on economic growth, while coal production significantly and negatively impacts on economic growth. This research is of great significance to the economic integration of the BRICS economies.
Keywords: Energy production; Energy consumption; Energy economics; Economic growth; BRICS; Energy Economy; Biofuel Production; Biofuel Consumption; Renewable energy